Effects of an elemental diet, inert bulk and different types of dietary fibre on the response of the intestinal epithelium to refeeding in the rat and relationship to plasma gastrin, enteroglucagon, and PYY concentrations. Issue 2 (February 1987) - Goodlad, R A; Lenton, W; Ghatei, M A; Adrian, T E; Bloom, S R; Wright, N A
Abstract : Refeeding starved rats with an elemental diet resulted in a marked increase in crypt cell production rate (CCPR) in the proximal small intestine but not in the distal regions of the gut. Little effect on CCPR was noted when inert bulk (kaolin) was added to the elemental diet. Addition of a poorly fermentable dietary fibre (purified wood cellulose) had little effect on intestinal epithelial cell proliferation except in the distal colon where it significantly increased CCPR. A more readily fermentable fibre (purified wheat bran) caused a large proliferative response in the proximal, mid, and distal colon and in the distal small intestine. A gel forming fibre only significantly stimulated proliferation in the distal colon; the rats in this group, however, did not eat all the food given. There was no significant correlation between CCPR and plasma gastrin concentrations, but plasma enteroglucagon concentrations were significantly correlated with CCPR in almost all the sites studied. Plasma PYY concentrations also showed some correlation with CCPR, especially in the colon. Thus while inert bulk cannot stimulate colonic epithelial cell proliferation fermentable fibre is capable of stimulating proliferation in the colon, and especially in the distal colon: it can also stimulate proliferation in the distal small intestine and it is likely that plasma enteroglucagon may have a role to play in this process.